A comparison of maternal fear of childbirth, labor pain intensity and intrapartum analgesic consumption between primiparas and multiparas: A cross-sectional study - Yongfang Deng; Yan Lin; Liyuan Yang; Qiuxia Liang; Bailing Fu; Huixian Li; Huizhu Zhang; Yan Liu (International Journal of Nursing Sciences, 2021)
Objectives: To describe and compare fear of childbirth and in-labor pain intensity between primiparas and multiparas and explore the association between the amount of actual pain relief and fear of childbirth. Methods: A convenience sampling method was used. A total of 260 women undergoing spontaneous or induced labor, including 97 primiparas and 163 multiparas, were recruited in a large academic specialized hospital in Guangzhou, China, from February 2018 to August 2019. The clinical data of maternal and neonatal were extracted from a structured electronic medical record system. Other demographic information, such as employment and family monthly income, was collected by a questionnaire. The Numeric Rating Scale (NRS) and the Chinese version of the Childbirth Attitude Questionnaire (C-CAQ) were applied to assess maternal in-labor pain intensity and fear of childbirth. The analgesic consumption and the frequency of manual boluses as rescue analgesia were stored and collected from the analgesia pump. Results: Eighty-two (84.5%) primiparas and ninety-nine (60.7%) multiparas received epidural analgesia (P < 0.001). In the epidural subgroup, the primiparous average fear of childbirth (36.46 ± 10.93) was higher than that of the multiparas (32.06 ± 10.23) (P = 0.007). However, multiparas reported more intense in-labor pain [8.0 (8.0, 9.0) vs. 8.0 (7.0, 8.0)], had more successful manual boluses per hour [2.68 (1.65, 3.85) vs. 1.77 (0.90, 2.47)], more hourly analgesic consumption [23.00 (16.00, 28.25) vs. 17.24 (11.52, 21.36) mL] and more average analgesic consumption [0.35 (0.24, 0.45) vs. 0.26 (0.19, 0.35) mL/(h·kg)] than the primiparas (P < 0.05). Spearman’s correlation analysis showed that the maximum in-labor pain was weakly positively correlated with fear of childbirth (r = 0.09) (P < 0.05), hourly analgesic consumption (r = 0.16) (P < 0.01) and average analgesic consumption (r = 0.17) (P < 0.05). No statistically significant association was uncovered between analgesic consumption and maternal fear of childbirth. Conclusions: Fear of childbirth is a potential predictor of labor pain intensity. Further study is needed to explore its role and value in pain management during delivery. Parity is not a determinant of pain relief use and should not be a preconceived preference of obstetric care team members to determine the distribution of epidural analgesia, especially when analgesia resources are insufficient.